Variants in the CYSLTR2 are associated with asthma, atopy markers and helminths infections in the Brazilian population. (June 2019) - dos S. Jesus, Talita; dos S. Costa, Ryan; Alcântara-Neves, Neuza Maria; Barreto, Maurício L.; Figueiredo, Camila Alexandrina
Highlights: Genetic variants in the CYSLTR2 gene are associated with asthma and severe asthma. Genetic variants in the CYSLTR2 gene are associated with atopy markers. Genetic variants in the CYSLTR2 gene are associated with helminth infection. Genetic variants in the CYSLTR2 gene may alter receptor expression in the lung and whole blood. Abstract: Background: Asthma is a chronic disease of the airways and its most common phenotype is characterized by a T2 type response with IgE production and inflammatory mediators in response to common allergens. Cysteinyl leukotrienes (CysLTs), LTC4, LTD4 and LTE4, are mediators known to possess important proinflammatory action. CysLTs can bind to the Cysteinyl leukotriene receptor type 2 (CysLTR2) and activate an inflammatory. Polymorphisms in CysLTR2 have been associated with asthma and atopy, although the mechanism is not clear. Objective: To evaluate the association between genetic polymorphisms in CYSLTR2 with asthma phenotypes, atopy markers and helminth infection. Methods: Genotyping was performed using a panel Illumina and carried out in 1245 participants of SCAALA program (Social Change, Asthma, Allergy in Latin American). Logistic regressions for asthma, helminth infections ( Trichuris trichiura and Ascaris lumbricoides ) and allergy markers (skin tests and IgE production) were performed using PLINK 1.9 software adjusted for sex, age, helminth infection and ancestry markers. Results: The G allele of rs1323556 was negatively associated with asthma in the additive model (OR 0.74, 95% CI 0.59–0.93) and in the dominant model (OR 0.71, 95% CI 0.53–0.74). The G allele of rs1575464 was also negatively associated with asthma in two genetic models, additive (OR 0.77, 95% CI 0.62–0.96) and dominant (OR 0.73, 95% CI 0.55–0.97). The G allele of rs61735175 was positively associated with asthma severity in the additive model (OR 1.72, 95% CI 1.07–2.77) and in the dominant model (OR 1.77, 95% CI 1.09–2.85). Five SNVs were associated with atopy markers and four SNVs were associated with helminth infections. Conclusion: Polymorphisms in the CYSLTR2 gene are associated with asthma, atopy markers and helminth infection in Brazilian individuals, which may lead to protection or risk for such conditions, however, more studies are needed to evaluate the functional of this variants here in described.